Religious Freedom for Indigenous Religion : A Case Study of Cemetery in Sapta Dharma - Qamariyah, Farihatul (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This study aims to analyze the encounter of cemetery cases related to Sapta Dharma indigenous religion and how it deals with the state’s regulation on the religious freedom in terms of expression and negotiation with the participants including the society as the victim, the local government, and the dynamic interaction among them. The framework of religious freedom by Elizabeth Shakman Hurd on Believing in Religious Freedom and the discourse of Human Rights and Religion within the debates by Rosalind. I. J. Hackett used to analyze the data. This study found that the case of cemetery in Sapta Dharma in some villages which are located in the region of Brebes Central Java underlines a significant notion on the expression of religious freedom for the Indigenous Religion. Religious freedom in the case of the needs of cemetary in Sapta Dharma also attaches the idea of majority and minority. Sapta Dharma as the minority and Islam as the majority of religion in Brebes create another standing point on the notion that minority is always in contact with such discrimination and oppression. Negotiation and mediation are two important things in putting off the case.